1029 Objectively-Measured Sleep Following a Time Restricted Eating Intervention in Adults With Obesity. (27th May 2020) - Simon, S L; Fleischer, J G; Manoogian, E N; Panda, S; Mashek, D G; Chow, L
Abstract: Introduction: Time-restricted eating (TRE), limiting food intake to a consistent daily window, is emerging as a novel weight loss intervention but impact of TRE on sleep remains unclear. Prior studies reported mixed results but are limited by subjective sleep measurements and lack of a randomized control group. Thus, we examined changes in actigraphy-measured sleep following a 12-week TRE protocol. Methods: Participants were 20 adults ages 18-65 years with BMI ≥24kg/ m2 . Participants were randomized to either TRE (8-hour eating window) or non-TRE (typical eating). At baseline and follow-up, all participants had anthropometric measurements, oral glucose tolerance test, logged eating occasions in a smartphone application, and wore an ActiGraph Link for two weeks. Independent samples t-tests compared groups on actigraphy-estimated sleep variables. Pearson correlations examined associations between sleep variables with health outcomes. Results: The TRE (N=11) and non-TRE groups (N=9) were predominantly female and had a baseline eating window of approximately 15 hours. There were no differences in actigraphy-assessed sleep variables at baseline or follow-up between groups. Participants did not significantly change their sleep from baseline to follow-up. Median weekday sleep duration was 6.2 hours at follow-up for all participants, suggesting insufficient sleep compared to the recommended 7-9 hours of sleep. Participants who obtained greater than the median weekday sleep duration at follow-up had significantly lower BMI, better insulin sensitivity (HOMA and Matsuda Index), and greater percent improvement in insulin sensitivity. Conclusion: Our data show that TRE does not significantly alter sleep behaviors in participants with obesity. However, longer sleep duration at follow-up was associated with lower BMI, better insulin sensitivity, and greater improvement in insulin sensitivity, indicating that sleep may be an important variable to consider in dietary interventions. Future research examining behavioral sleep strategies in combination with TRE is needed to evaluate whether improved sleep leads to better weight loss and glycemic outcomes for individuals with obesity. Support: This work was support by the Healthy Foods Healthy Lives program (17SFR-2YR50LC to LC) and the National Institutes of Health (NIH National Center for Advancing Translational Sciences, UL1TR002494).